2018
DOI: 10.1136/bmjopen-2017-020571
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and cigarette expenditure among US households: results from 2010 to 2015 Consumer Expenditure Survey

Abstract: ObjectivesTo examine (1) the association between household socioeconomic status (SES) and whether a household spends money on cigarettes and (2) socioeconomic variations in proportion of total household expenditure spent on cigarettes among smoking households.MethodsWe pooled data from six consecutive years, 2010–2015, of the Consumer Expenditure Interview Survey. The interviews involved a structured questionnaire about household income, demographics and expenditures including expenditure on cigarettes. Househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…However, smoking as the major reason for the finding of short stature should be interpreted with caution as smoking is known to be a proxy marker of socioeconomic status, which has long been known to influence childhood growth. 28,29 In the present study, we showed that Swedish infants and children grew taller than expected based on the WHO growth standard.…”
Section: A Selected Reference Populationsupporting
confidence: 55%
See 1 more Smart Citation
“…However, smoking as the major reason for the finding of short stature should be interpreted with caution as smoking is known to be a proxy marker of socioeconomic status, which has long been known to influence childhood growth. 28,29 In the present study, we showed that Swedish infants and children grew taller than expected based on the WHO growth standard.…”
Section: A Selected Reference Populationsupporting
confidence: 55%
“…Our results showed individuals born to mothers who smoked during pregnancy to be on average as much as 2 cm shorter as adults than those born to non‐smoking mothers. However, smoking as the major reason for the finding of short stature should be interpreted with caution as smoking is known to be a proxy marker of socioeconomic status, which has long been known to influence childhood growth …”
Section: Discussionmentioning
confidence: 99%
“…However, socioeconomic factors such as level of education, marital status, employment status, and poverty have been shown to be influenced by age, 42,43 sex, 44,45 and race. 46,47 In addition, because traditional cigarette use is influenced by socioeconomic factors, 48-52 it is logical that these factors would also translate to the use of e-cigarettes. Therefore, the statistical models with marital status, education level, employment status, and poverty-income ratio as exposures were adjusted for the sociodemographic factors of age, sex, and race.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, household expenditure data may be useful to explore trends and patterns of behaviours across dwelling types. Other studies have also used expenditure data to examine tobacco use (61)(62)(63) , gambling (62,64,65) , alcohol purchasing (62,66) and food purchasing (2,62,67) . This type of data can be an important tool to inform and develop health strategies and policies in various areas (68)(69)(70) .…”
Section: Strengths and Limitationsmentioning
confidence: 99%